First measurement of the top quark pair production cross section in proton-proton collisions at s $$ \sqrt{s} $$ = 13.6 TeV - The CMS collaboration; A. Tumasyan; W. Adam; J. W. Andrejkovic; T. Bergauer; S. Chatterjee; K. Damanakis; M. Dragicevic; A. Escalante Del Valle; P. S. Hussain; M. Jeitler; N. Krammer; et al. (Journal of High Energy Physics, 2023)
Abstract The first measurement of the top quark pair ( t t ¯ $$ t\overline{t} $$ ) production cross section in proton-proton collisions at s $$ \sqrt{s} $$ = 13.6 TeV is presented. Data recorded with the CMS detector at the CERN LHC in Summer 2022, corresponding to an integrated luminosity of 1.21 fb −1, are analyzed. Events are selected with one or two charged leptons (electrons or muons) and additional jets. A maximum likelihood fit is performed in event categories defined by the number and flavors of the leptons, the number of jets, and the number of jets identified as originating from b quarks. An inclusive t t ¯ $$ t\overline{t} $$ production cross section of 881 ± 23 (stat + syst) ± 20 (lumi) pb is measured, in agreement with the standard model prediction of 924 − 40 + 32 $$ {924}_{-40}^{+32} $$ pb.